1992
DOI: 10.1007/bf03344932
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the concentrations and binding properties of sex steroid binding protein and corticosteroid-binding globulin in HIV+patients

Abstract: The abnormal concentrations of steroid hormones and free fatty acids in the plasma of HIV-infected subjects are associated with qualitative and quantitative alterations in two of the major steroid hormones carrier proteins, sex steroid-binding protein (SBP) and corticosteroid-binding globulin (CBG). The properties of SBP and CBG in the sera of two age-matched groups of 67 men healthy blood donors (controls) and 64 HIV+subjects: 11 CDC group II and III (ASY), 6 CDC group IVA and 47 groups IV C1+D (AIDS) were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 29 publications
2
27
1
Order By: Relevance
“…Increased SHBG levels were seen in previous studies of HIVinfected men, which suggests the importance of the measurement of bioavailable testosterone levels in this population [3,24]. Although SHBG levels were on average within normal limits in our patients, 25% of HIV-infected men had increased levels.…”
Section: Discussioncontrasting
confidence: 50%
“…Increased SHBG levels were seen in previous studies of HIVinfected men, which suggests the importance of the measurement of bioavailable testosterone levels in this population [3,24]. Although SHBG levels were on average within normal limits in our patients, 25% of HIV-infected men had increased levels.…”
Section: Discussioncontrasting
confidence: 50%
“…Importantly, many studies have only reported total testosterone levels, which may not accurately reflect free bioactive testosterone concentrations because of increased sex hormone-binding globulin concentrations among men with HIV infection [3,9].…”
mentioning
confidence: 97%
“…All these side effects have been reported in association with antiretroviral therapy also. SHBG, like other globulins, are raised in AIDS and HIV infection 13,14 . It is unclear if HAART affects SHBG.…”
Section: Discussionmentioning
confidence: 99%